Correction: Computationally guided discovery of a reactive, hydrophilic trans-5-oxocene dienophile for bioorthogonal labeling. Issue 35 (29th August 2017) - Lambert, William D.; Scinto, Samuel L.; Dmitrenko, Olga; Boyd, Samantha J.; Magboo, Ronald; Mehl, Ryan A.; Chin, Jason W.; Fox, Joseph M.; Wallace, Stephen
Abstract : Correction for 'Computationally guided discovery of a reactive, hydrophilic trans -5-oxocene dienophile for bioorthogonal labeling' by William D. Lambert et al., Org. Biomol. Chem., 2017, 15, 6640–6644.